2011
DOI: 10.1007/s10924-011-0391-4
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation Behavior of Composite Films with Poly (Vinyl Alcohol) Matrix

Abstract: The main objective of this study was to develop biodegradable, composite materials, based on poly (vinyl alcohol), bacterial cellulose and chitosan for possible application in packaging industry. Two composite materials were prepared, one containing poly (vinyl alcohol) (PVA) and bacterial cellulose (BC), named PVA/BC, and the other containing PVA, BC but also chitosan (CTS), named PVA/BC/CTS. The biodegradation behavior was studied in a fed-batch bioreactor, in aerobic and anaerobic conditions, using activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Of particular interest are treatments with food-grade compounds such as sorbic acid (Dobre et al 2012) or the bio-based cationic polymer chitosan (Tome et al 2013;Velasquez-Cock et al 2014;Li et al 2015b), which nevertheless can improve the ability of the package to protect the food inside it against decay. Also, there has been much interest in utilizing nanomaterials such as colloidal silver particles in combination with nanocellulose for antimicrobial activity in packaging (Amini et al 2016;Yan et al 2016).…”
Section: Drug Release and Antimicrobial Packagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest are treatments with food-grade compounds such as sorbic acid (Dobre et al 2012) or the bio-based cationic polymer chitosan (Tome et al 2013;Velasquez-Cock et al 2014;Li et al 2015b), which nevertheless can improve the ability of the package to protect the food inside it against decay. Also, there has been much interest in utilizing nanomaterials such as colloidal silver particles in combination with nanocellulose for antimicrobial activity in packaging (Amini et al 2016;Yan et al 2016).…”
Section: Drug Release and Antimicrobial Packagingmentioning
confidence: 99%
“…Kibedi-Szabo et al (2012), on the other hand, demonstrated the biodegradability of composite materials comprised of poly-(vinyl alcohol), bacterial cellulose, and chitosan. Biodegradation was observed to take place within the composites, not just at their surface.…”
Section: Biodegradabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical structure of chitosan is very similar to that of cellulose, except for the replacement of one NH 2 group instead of OH on the glucose molecule. Recent studies revealed that it is widely used for medicine, edible packaging or coating, food additives, cosmetic, water treatment, and antifungal agents. …”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of the biodegradation of composites that contained bacterial cellulose. A starch/BC composite had degradation measured by determining the weight loss after soil burial and it was found that composites achieved 69% degradation within 3 weeks of burial . Bacterial cellulose contents and choice of culture medium were found to influence the degradation of poly­(vinyl alcohol) (PVA)/BC composites when exposed to a single fungal strain in laboratory culture; however, in this study, biodegradation was only studied qualitatively and no overall measurement of biodegradation was made …”
Section: Introductionmentioning
confidence: 90%